2011
DOI: 10.1080/09084282.2010.523381
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Tower of Hanoi Performance: Interactive Effects of Psychopathic Tendencies, Impulsive Response Styles, and Modality

Abstract: Previous research has demonstrated that performance on the computerized Tower of Hanoi is lower than performance on the manual Tower of Hanoi. The present study was conducted to elucidate potential factors that contribute to performance differences across modalities. Personality characteristics related to psychopathy and impulsive response styles were hypothesized to be correlates of poor performance on the computerized version of the Tower of Hanoi, which is a problem-solving task that requires working memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Moreover, in populations with antisocial personality disorder and psychopathic behaviour, impairments in executive function have often been observed (Brazil et al, 2011;Salnaitis, Baker, Holland, & Welsh, 2011). This raises the possibility that individual differences in executive functions could be involved in the modulation of other cognitive-affective process.…”
mentioning
confidence: 99%
“…Moreover, in populations with antisocial personality disorder and psychopathic behaviour, impairments in executive function have often been observed (Brazil et al, 2011;Salnaitis, Baker, Holland, & Welsh, 2011). This raises the possibility that individual differences in executive functions could be involved in the modulation of other cognitive-affective process.…”
mentioning
confidence: 99%
“…There is another problem regarding cognitive measures that is increasingly attracting attention in science: the use of a variety of strategies in completing the items of a measure (e.g., Geiser, Lehmann, & Eid, 2006;Perret, Bailleux, & Dauvier, 2011;Salnaitis et al, 2011;Schweizer, 2009). The use of strategies can become a problem if participants are expected to follow the prescribed strategy.…”
Section: Exchange Test Analysismentioning
confidence: 99%
“…Impurity can be due to similarity among the items or trials or due to the participants' using different strategies in completing the items of the measure. There are reports of participants deviating from the expected processing strategy and this way changing the nature a measure (e.g., Patensko & Altman, 2010;Salnaitis, Baker, Holland, & Welsh, 2011). Impure measures lead to systematic variance that is irrelevant variance besides true variance.…”
Section: Introductionmentioning
confidence: 99%
“…In order to successfully achieve their desired goals, these individuals need the ability to foresee possible consequences of their actions, and thus would need intact or superior planning ability. Salnaitis, Baker, Holland, and Welsh (2011) found evidence for such relationship. They examined performance on a computerised version of the Tower of Hanoi to assess planning ability, but also response style, in a sample of undergraduate university students, assessed for psychopathy using the PPI.…”
Section: Cool Executive Function In Successful Psychopathymentioning
confidence: 94%
“…On the other hand, noncriminal samples have a mix of male and female participants and reveal intact performance on planning tasks. For example, Salnaitis et al (2011) found that undergraduate participants who scored high on psychopathy performed better on the Tower of Hanoi than low and medium psychopathy scorers. Interestingly, in contrast to criminal offender samples, the sample was predominately female (73%).…”
Section: Femalesmentioning
confidence: 99%